Pelatihan Metode Jarimatika dalam Meningkatkan Kemampuan Berhitung Siswa Sekolah Dasar - Firliani, Firliani; Suciaty, Nella (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
This training activity is a community service activity carried out by PKBM Hati Nurani Bangsa located in Trajaya Village, District. Palasah, District. Majalengka. The target in the implementation of this training is the second grade elementary school students. This method of using jarimatika is an easy and cheap method that is very fun. Students only count using their fingers and do not use writing instruments. This is to be able to change the difficult mathematical paradigm into something fun. In addition to that, the increase in numeracy and students' ability to count can be improved and trained. The use of this technique or method of arithmetic is expected to improve numeracy skills in calculating addition and subtraction. Some of the constraints are limited time because in 1 implementation meeting is only 1 hour. Among the results of this research, it was seen that the participants were very enthusiastic and the results of the evaluation showed that there was an increase in the students' ability to count in doing calculations using fun and fast math. Through this training, you can change the difficult mathematical paradigm into something fun.